Burkina Faso : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2007)
Burkina Faso's request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility is discussed. The proposed new Poverty Reduction and Growth Facility (PRGF) program would help anchor macroeconomic stability and support Burkina Faso's poverty reduction and growth strategy. Macroeconomic performance under the previous PRGF arrangement has been good. Average real GDP growth has been above 6 percent, inflation has been low and stable, and the current account has improved. Increasing domestic revenues would create fiscal space for poverty-reducing expenditures while keeping debt sustainable.